DEVELOPMENT AND CHANGES IN COMPETITION LAW IN THE DIGITAL WORLD: SHIFTS IN THE LEGISLATIONS OF UZBEKISTAN AND THE EUROPEAN UNION - Doniyor Abduazizov (Journals Park Publishing, 2024)
Competition law metrics generally understand a market as a specific good or service provided by a supplier and received by a customer/consumer. This understanding was based on the economic rules of supply and demand and could be found classical in all market economy jurisdictions. This understanding changed with the advent of digital products and the digital economy. The digital economy is now commonly understood as a new quality of economic life driven by the massive growth of digitalization and other technologies. And in this new economic reality, the need to apply new competition rules is questioned. Thus, the economic indicators relied upon by legal and economics science so far have lost their meaning in assessing the boundaries of the digital market.
Keywords: competition law, digitalization, online platforms (marketplaces), market aggregators, market boundary, free goods and services etc.